Equal or Not? On the Material Aspect of Equality of European Parliament Elections in Poland - Glajcar, Rafał (Political Preferences, 2014)
This article focuses on the issue of equality of elections, in the context of the 2014 European Parliament election in Poland. Most often the definition of principles of elections' equality comes down to emphasizing its two aspects: the formal one and the material one. The first of them refers to guaranteeing each person with the active voting right the same number of votes. The material aspect of the equality principle is connected with striving to guarantee the same "voting power" to the election participants. Most briefly, it means that a given number of people elect as many representatives as another group with the same numerical strength. The main aim of this article is focus on the material aspect of implementing the principle of equality in EP elections. In the article will be emphasized three issues decisive for the specific features of the electoral system (electoral districts, election threshold and electoral formula), at the same time influencing the range of implementation of the material equality of elections. General findings will be confronted with empirical data, which will allow to formulate conclusions about the degree to which the European Parliament election conducted in Poland on 25th May 2014 met the principle of material equality.